2017
DOI: 10.1080/09168451.2016.1246175
|View full text |Cite
|
Sign up to set email alerts
|

α-Defensin 5 gene expression is regulated by gut microbial metabolites

Abstract: α-Defensin 5 is important to both maintenance of a gut microbiota and host immunity. While previous reports have shown that gut bacteria are able to upregulate α-defensin 5 through Toll-like receptor signaling, we demonstrate here that α-defensin 5 expression can also be regulated by microbial metabolites. Among these, lactate appeared to significantly suppress α-defensin 5 gene transcription. Actually, fractions of <3 kD compounds obtained from the ceca of SPF mice were suppressed α-defensin 5 gene transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, in the small intestine they are released into the intestinal lumen, which are likely to be delivered into the colonic lumen. Expression of α-defensins are known to be down regulated in Crohn’s disease 5 and by intestinal microbial metabolites such as lactate 18 . In the present study, our data show for the first time, that chronic EtOH feeding down regulates the expression of Defa4 , Defa5 and Defa6 genes in mouse ileum.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the small intestine they are released into the intestinal lumen, which are likely to be delivered into the colonic lumen. Expression of α-defensins are known to be down regulated in Crohn’s disease 5 and by intestinal microbial metabolites such as lactate 18 . In the present study, our data show for the first time, that chronic EtOH feeding down regulates the expression of Defa4 , Defa5 and Defa6 genes in mouse ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by using a human-derived reporter cancer cell line, Sugi et al investigated the transcription of Defa5 after challenge with the bacterial ligands LPS, the synthetic lipopeptide P3CSK4 or with the bacterial metabolites acetate, lactate, butyrate, and propionate. Among these molecules, lactate strongly suppressed the transcription of Defa5 while propionate and butyrate were suppressive only at a high concentration (9 mM) (198). However, this intestinal cell line represents absorptive epithelial cells, and their defensin expression capacities are lower when compared to Paneth cells.…”
Section: Microbial-derived Components and Molecules Implicated In Hdpmentioning
confidence: 87%
“…Accordingly, using mousederived small intestinal organoids, Farin et al showed that Paneth cell degranulation did not occur after stimulation with bacterial agents, but rather after direct induction with IFN-γ or a supernatant derived from stimulated iNKT cull culture (138). Similarly, the SCFA butyrate was shown to directly enhance the production of Defa1 in isolated crypts from the small intestine (165), but it is unclear whether Paneth cells could be stimulated by this fermentation product in the small intestine in vivo, where the concentration of butyrate is relatively low (165,198). Furthermore, by using a human-derived reporter cancer cell line, Sugi et al investigated the transcription of Defa5 after challenge with the bacterial ligands LPS, the synthetic lipopeptide P3CSK4 or with the bacterial metabolites acetate, lactate, butyrate, and propionate.…”
Section: Microbial-derived Components and Molecules Implicated In Hdpmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel discoveries have been made with regard to the structure, functional diversity, and effect on host microbiota of these peptides (Sugi et al, 2017; Zhang, 2017). Many of these discoveries point to a much greater role for defensins in host health and immunity than previously thought.…”
Section: Discussionmentioning
confidence: 99%